2018
DOI: 10.1111/bor.12313
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy of small mammal bone accumulations generated by the Chaco owl (Strix chacoensis, Strigiformes) from the Monte Desert (Mendoza, Argentina): a contribution to South American archaeological and palaeontological studies

Abstract: The present study analyses the taphonomic features of recent small mammal bone and teeth accumulations recovered from pellets generated by Strix chacoensis in a Natural Protected Area in the central Monte Desert of Mendoza, Argentina. In order to identify the taphonomic signature of this predator in the formation of zooarchaeological and palaeontological accumulations, taxonomic profiles, relative abundances, bone breakage patterns and digestive corrosion were evaluated. Taphonomic results locate S. chacoensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
2
10

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 33 publications
(40 reference statements)
5
16
2
10
Order By: Relevance
“…This methodology was followed with most samples of South American predators. Fernández-Jalvo et al (2016) and recently suggested that modifications on incisors and molars were enough to give pertinent information; these updated criteria were used in the evaluation of South American samples of G. melanoleucus, G. polyosoma and S. chacoensis (López et al, 2017a(López et al, , 2018.…”
Section: Current Status Of the Taphonomy Of Small Mammalsmentioning
confidence: 99%
See 4 more Smart Citations
“…This methodology was followed with most samples of South American predators. Fernández-Jalvo et al (2016) and recently suggested that modifications on incisors and molars were enough to give pertinent information; these updated criteria were used in the evaluation of South American samples of G. melanoleucus, G. polyosoma and S. chacoensis (López et al, 2017a(López et al, , 2018.…”
Section: Current Status Of the Taphonomy Of Small Mammalsmentioning
confidence: 99%
“…For example, A. cunicularia yields greater abundance of pelves (Gómez, 2007;Montalvo and Tejerina, 2009) while A. flammeus shows higher values of radii and lesser values in the other elements (Gómez, 2007), and S. chacoensis produces a pattern similar to that of the average strigiforms but with lower values (López et al, 2018).…”
Section: Nocturnal Raptorsmentioning
confidence: 99%
See 3 more Smart Citations